Pt - g-C3N4 - (Au/TiO2): electronically integrated nanocomposite for solar hydrogen generation - Devaraji, Perumal; Gopinath, Chinnakonda S. (International Journal of Hydrogen Energy, 2018)
A potential nanocomposite photocatalyst was designed by integrating Pt nanoclusters (co catalyst and electron sink) with graphitic carbon nitride (g-C3N4 (gcn)) (charge diffusion) and 0.5 wt % Au containing Au-TiO2 (AuT) (plasmonic on semiconductor) for solar water splitting (SWS). Variety of Pt-gcn-AuTiO2 compositions has been evaluated for SWS under one sun conditions. Complexity of the photocatalyst was increased systematically from Au-TiO2, gcn-TiO2 to Pt-gcn-Au-TiO2 to explore the influence of different combinations. Electronic integration of charge separation/diffusion component (gcn) with light absorbing sensitizer components (Au and gcn), and co-catalyst (Pt) seems to be the critical factor to improve hydrogen yield (HY) or overall efficiency. Although addition of gcn increase the HY of composites, there is no SWS activity observed on bare TiO2 or gcn. Au or Pt on gcn enhances the charge separation effectively and interface between Au and/or Pt with gcn works as the Schottky barrier. A monodispersion of Au over TiO2 and Pt nanoclusters over gcn/AuTiO2 composite lead to the maximum solar hydrogen yield (1.52 mmol/h g) with an apparent quantum yield (AQY) of 7.5%. Photoelectron and photoluminescence spectral studies confirm the electron transfer from Au to gcn, and Au and/or gcn to titania. A thorough physico-chemical investigation of various composites underscores the electronic integration aspects of the nanocomposite towards storage of electrons in the Pt co-catalyst and hence an effective charge separation and an increase in AQY. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Electronic integration; Photocatalysis; Schottky barrier; Solar hydrogen; water splitting